The light side of proto-cluster galaxies at z ∼ 4. Issue Volume 15:Issue S359(2020) (March 2019) - Ito, Kei
Abstract: Overdense regions at high redshift, which are often called "protoclusters", are thought to be a place where the early active structure formations are in progress. Thanks to the wide and deep-sky survey of Hyper Suprime-Cam Subaru Strategic Program, we have selected 179 protocluster candidates at z ˜ 4, enabling us to statistically discuss high- z overdense regions. I report results of the HSC-SSP protocluster project, focusing on a couple of results on the bright-end of protocluster galaxies. We identify the UV-brightest galaxies, which are likely progenitors of Brightest Cluster Galaxies. We find that these are dustier and larger than field galaxies. This suggests that galaxies in protoclusters have experienced different star formation histories at z ˜ 4. Also, the UV luminosity function of galaxies in protoclusters (PC UVLF) has a significant excess on the bright-end from field UVLF. The PC UVLF suggests that protoclusters contribute ˜ 5 – 16% of the total cosmic SFRD at z ˜ 4. The result implies that early galaxy formation occurs in protoclusters.